The Validity of Cutaneous Body Image as a Construct and as a Mediator of the Relationship Between Cutaneous Disease and Mental Health - Sarah B. Hinkley; Shayla C. Holub; Alan Menter (Adis, Springer Healthcare, 2020)
Abstract Introduction Cutaneous body image (CBI) is a construct encompassing how individuals perceive their hair, skin, and nails. Negative CBI has been related to negative psychological outcomes and body image concerns. The first aim of our study was to further validate CBI as a construct. Second, as individuals with dermatologic conditions are at an increased risk for anxiety and depression, the study examined CBI as a mediator of the relationships between having a skin condition and anxiety and depression. Methods A convenience sample of clinical participants with dermatologist-validated diagnoses of psoriasis, atopic dermatitis, or acne who were currently taking systemic medication (n = 128) were matched to a sample of comparison participants without skin conditions (n = 128) on self-reported gender, ethnicity, developmental stage, and weight status (body mass index). All participants reported on their CBI, self-esteem (global, appearance-related, and weight-related), body dissatisfaction, drive for thinness, dietary restraint, anxiety, depression, and demographic characteristics. Results Cutaneous body image was more negative in those respondents with skin conditions (regression analysis B = − 0.61, standard error 0.23, p = 0.008), demonstrating the criterion-related validity of the measure. CBI was significantly correlated with global (r  = 0.39, p  < 0.001) and appearance-related self-esteem (r  = 0.50, p  < 0.001), which establishes convergent validity. CBI was not significantly related to a drive for thinness (r  = − 0.12, p  = 0.06) or to dietary restraint (r  = − 0.05, p  = 0.39), supporting discriminant validity. CBI mediated the relationships between having a dermatologic condition and anxiety [point estimate of indirect effect 0.07, 95% confidence interval (CI) 0.02, 0.15] and depression (point estimate of indirect effect 0.04, 95% CI 0.01, 0.08). Conclusions The measure of CBI has been further validated. Dermatologists must be aware that various dermatoses may impact patient mental health via the mechanism of negative CBI.